2020
DOI: 10.3390/nu12092626
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Autophagy-ER Stress Axis in High Fat/Carbohydrate Diet-Induced Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease that can progress from simple hepatic steatosis to nonalcoholic steatohepatitis (NASH), and even further to liver cirrhosis or liver cancer. Overconsumption of high fat and/or carbohydrate are among the most common lifestyle factors that drive the development and progression of NAFLD. This review evaluates recent reports on the involvement of autophagy and endoplasmic reticulum (ER) stress in the pathogenesis of NAFLD. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Autophagy is an intracellular pathway that targets and delivers cellular components such as organelles and protein aggregates to lysosomes for degradation. Autophagy dysfunction has been identified as a key factor in the pathogenesis of several diseases, ranging from neurodegenerative disorders, such as Parkinson disease to metabolic disorders, such as nonalcoholic fatty liver disease (NAFLD) [ 1 , 2 , 3 ]. Indeed, many of the functions of autophagy are impaired in NAFLD, including its ability to regulate cellular insulin sensitivity, mediate hepatocyte resistance to harmful stimuli such as oxidants and cytokines, and metabolize cellular lipid stores by lipophagy [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an intracellular pathway that targets and delivers cellular components such as organelles and protein aggregates to lysosomes for degradation. Autophagy dysfunction has been identified as a key factor in the pathogenesis of several diseases, ranging from neurodegenerative disorders, such as Parkinson disease to metabolic disorders, such as nonalcoholic fatty liver disease (NAFLD) [ 1 , 2 , 3 ]. Indeed, many of the functions of autophagy are impaired in NAFLD, including its ability to regulate cellular insulin sensitivity, mediate hepatocyte resistance to harmful stimuli such as oxidants and cytokines, and metabolize cellular lipid stores by lipophagy [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, advanced glycation end products (AGE) can be a potential biomarker of the NAFLD stage since AGE showed good criteria for dividing patients with minimal steatosis (BARD score 0–1) vs. moderate steatosis (BARD score 2–4) [ 72 ]. Furthermore, a high intake of fat and carbohydrates can induce ER stress, and dysfunction of ER develops metabolically-driven NAFLD progress [ 73 , 74 ]. Although this study revealed that HCA had therapeutic effects by suppressing lipid accumulation and apoptosis in liver cells, other components may be effective to NAFLD since recent clinical trials suggest that protein oxidation/glycation and ER stress are involved in liver fibrosis in NAFLD [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The steatosis itself does not pose a significant risk, but it can trigger inflammation that leads eventually to nonalcoholic steatohepatitis (NASH) and then to cellular injury and liver fibrosis (Lebeaupin et al, 2018; Zhou, Fouda, Li, Zhang, & Ye, 2020). Although the mechanisms behind NAFLD are not completely understood, ERS has been shown to play an important role in its pathogenesis (Song & Malhi, 2019; Zhou et al, 2020). The excess of lipids in cells heightens the level of oxidative stress that in turn disrupts protein folding leading to ERS (Fujii, Homma, Kobayashi, & Seo, 2018).…”
Section: Liver Diseasesmentioning
confidence: 99%